'Urbs, 'Urb Girls, and Martine Delvaux's Rose amer. (December 2019) - Morgan, Ceri
Abstract : This article considers representations of exurban spaces in Martine Delvaux's Rose amer (2009), positioning it in relation to a broader take-up of "regional" spaces in Québec fiction. It argues that Delvaux's novel is prescient in its blurring of distinct spatial categories. Examining how Rose amer parallels setting and characters, the article argues that it offers an intervention in the politics of memorialization. This is achieved through a focus on the standardized and reproducible, so that the vernacular domestic geographies featured within the novel become everyday monuments to the violence which is daily perpetrated against girls and women.